An In-Depth Analysis of White-Collar Crimes in The Financial Sector of Dubai: Legal Frameworks and Collaborative Solutions - Komalasari, Rita; Mustafa, Cecep (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2024)
This study aims to identify specific legal loopholes and regulatory deficiencies that contribute to white-collar crime, with the goal of advocating for adaptive legal reforms and a collaborative approach to strengthen legal frameworks. The specific focus is on the prevalence of white-collar crime in the financial sector of the emirate, given Dubai's rapidly growing economy. Therefore, this study addresses the potential exploitation of legal frameworks and regulatory gaps to offer a contextualised analysis of the contributing factors during the economic expansion of the emirate. A comprehensive literature review was applied to identify existing gaps in understanding, with a focus on the distinctive challenges faced by Dubai. The intention was to provide a thorough understanding of white-collar crime in the financial sector with an emphasis on the mechanisms through which legal loopholes and regulatory shortcomings could facilitate such offences. The identification of the vulnerabilities led to the provision of actionable insights for policymakers, regulatory authorities, and stakeholders to fortify legal infrastructure and prevent financial misconduct. The results deepened our understanding of the challenges associated with white-collar crime in Dubai. They provided practical insights for mitigating future risks by presenting a roadmap for policymakers to combat the growing nature of financial offences in the region. In conclusion, this study highlights the urgent need for adaptive legal reforms and enhanced regulatory measures to address the vulnerabilities within Dubai's financial sector.